Who feels inferior? A test of the status anxiety hypothesis of social inequalities in health - Richard Layte; Christopher T. Whelan (The Economic and Social Research Institute (ESRI), 2014)
The empirical association between income inequality, population health and other social problems is now well established and the research literature suggests that the relationship is not artefactual. Debate is still ongoing as to the cause of this association. Wilkinson, Marmot and colleagues have argued for some time that the relationship stems from the psycho-social effects of status comparisons. Here, income inequality is a marker of a wider status hierarchy that provokes an emotional stress response in individuals that is harmful to health and well-being. We label this the "status anxiety hypothesis". If true, this would imply a structured relationship between income inequality at the societal level, individual income rank and anxiety relating to social status. This paper sets out strong and weak forms of the hypothesis and then presents three predictions concerning the structuring of "status anxiety" at the individual level, given different levels of national income inequality and varying individual income. We then test these predictions using data from a cross-national survey of over 34,000 individuals carried out in 2007 in 31 European countries. Respondents from low inequality countries reported less status anxiety than those in higher inequality countries at all points on the income rank curve. This is an important precondition of support for the status anxiety hypothesis and may be seen as providing support for the weaker version of the hypothesis. However, we do not find evidence to support a stronger version of the hypothesis which we argue requires the negative effect of income rank on status anxiety to be exacerbated by increasing income inequality.
Keywords: 330; health inequalities; income inequality; psycho-social; status anxiety; multi-level models; comparative country data